Massive preparation and characteristics of submicron dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50) - Lei Xiao; Liming Zhang; Weiwei Zhang; Guangpu Zhang; Yubing Hu; Suwei Wang; Gazi Hao; Wei Jiang (FirePhysChem, 2021)
In order to make the shape of raw dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50) particles more regular and suitable for coating, modification, charging and other applications, submicron TKX-50 was prepared with average particle size of 120 nm through a low-temperature ball milling technique by 1 kg per batch in this study. The morphology and structure of prepared submicron TKX-50 were characterized by scanning electron microscopy (SEM), X-ray diffractometer (XRD) and fourier transform infrared spectroscopy (FT-IR). The thermal decomposition properties were analyzed by thermogravimetric analysis (TG) and differential scanning calorimetric (DSC) techniques, and the thermal decomposition process of submicron TKX-50 was investigated using TG-FTIR technology, by which the gas products would be detected. Moreover, the mechanical sensitivities were also evaluated. The results showed that the prepared submicron TKX-50 was spherical in shape and the structures of crystal and molecule had no change compared to raw TKX-50. The thermal decomposition temperature of submicron TKX-50 was shifted about 14-18 ºC towards lower temperature, while its activation energy value was increased according to the Kissinger method and the Kissinger-Akahira-Sunose (KAS) method. The most-abundant decomposition products of submicron TKX-50 were HCN, CO2, N2O, NH3 and a small amount of H2O. In addition, submicron TKX-50 showed excellent safety, which guaranteed its predictable applications on ammunitions with high energy and low sensitivity.